La trasmisión de palabras de origen uchinaguchi mediante las principales características culturales okinawenses y su recepción en la comunidad nikkei de Lima, 2018 - Carrasco, Jhonattan (2021)
The largest part of Lima's Nikkei community is composed of Okinawan descendants. Therefore, the arts, gastronomy, and rites of Okinawa are cultural characteristics that are part of the lives of the members of this community. Although the native language of Okinawa (Uchinaguchi) is in danger of extinction, this paper exhibits that the practice of these cultural characteristics, at home and in community events and workshops, generates the transmission and reception of Uchinaguchi words ("uchinaguisms") in Lima's Nikkei community.